Spatial health inequality and regional disparities historical evidence from Malaria in Italy - Marco Percoco (REGION, 2021)
Geography and the quality of the environment may have long lasting effects on the living standards of individuals and this, in its turn, may affect even substantially the distribution of income and regional disparities. In this paper I consider malaria as a measure of "bad geography" and propose some evidence showing that it was a major determinant of the health of individuals (as measured by the height of conscripts) and its disparities between individuals and regions in Italy. In particular, to estimate the relationship between malaria exposure and height, I rely on the "fetal origins hypothesis", that is I hypothesize that exposure to malaria in utero or during childhood has persistent effects on health. Periods under scrutiny in this paper are the last two decades of the XIX century, a period without major public health interventions, and the years around the eradication era in the 1950s. My results support the hypothesis that geographically targeted policies may reduce health inequality between regions and within regions.
Keywords: 330; Health inequality; place-based policies; spatial disparities; regional develop-ment; malaria; height